Global Research on ESG in Accounting Science: Bibliometrics analysis - Yusron Difinubun; Dhini Dwi Nastiti (Financial and Accounting Indonesian Research, 2024)
ESG is the latest issue in the accounting science discourse in sustainable development. This study aims to analyse the trend of research focus, number of publications, number of citations, classification based on aspects (research field, journal, researcher), network visualization from aspects (co-occurrence, co-authorship), publication cluster in terms of aspects (co-occurrence, co-authorship), overlay visualization, and density visualization will be described research topics related to carbon emissions in accounting science using bibliometric analysis. Data from Dimension describes the level of research interest in carbon emissions from 1999 to 2023. The data was collected and analysed with VOSviewer to see the relationship of research objects, paper distribution, and author collaboration, and using Excel 2023 for research profiles. The results of Bibliometric analysis with VOSviewer show that the novelty for research on the topic of ESG in Accounting Science in the coming years is ESG associated with Board Gender Diversity. Earnings Management, ESG associated with Board Diversity, ESG Performance, Board Size, Board Diversity, Cost, Information Asymmetry, Audit Committee.